Design and fabrication of crushing machine / Mohamad Amirul Afieq Danial Azlan and Ahmad Najmie Rusli - Azlan, Mohamad Amirul Afieq Danial; Rusli, Ahmad Najmie (School of Mechanical Engineering, 2023)
This study presents the design and fabrication of a crushing machine, motivated by the escalating production rates and consequential accumulation of waste materials such as brick, glass, and cement, all characterized by brittleness. The proliferation of such waste materials has engendered multifaceted challenges spanning industrial, environmental, and economic domains at a global scale. The primary complications arise from the voluminous space required for waste storage, exorbitant costs associated with waste transportation to recycling facilities, and the substantial labour force needed to manage the accumulated waste. These issues are especially pronounced for smaller contractors, amplifying the magnitude of their operational and financial burdens. In response to these challenges, this project presents a crushing machine that operates on fundamental mechanical principles. The mechanism incorporates angular motion and piston-like functions driven by an electric motor. The hammer, for instance, moves from the apex to the nadir, effectively comminuting the waste materials upon impact. In summation, the development of this crushing machine offers a viable resolution to the intricate challenges confronting industrial sectors. It promises cost reductions, operational efficiencies, and enhanced waste management capabilities, rendering it a promising asset within the industry.